Serum I‐FABP as marker for enterocyte damage in coeliac disease and its relation to villous atrophy and circulating autoantibodies. Issue 4 (7th January 2013) - Adriaanse, M. P. M.; Tack, G. J.; Passos, V. Lima; Damoiseaux, J. G. M. C.; Schreurs, M. W. J.; van, K.; Riedl, R. G.; Masclee, A. A. M.; Buurman, W. A.; Mulder, C. J. J.; Vreugdenhil, A. C. E.
Summary Background Enterocyte damage is the hallmark of coeliac disease (CD) resulting in malabsorption. Little is known about the recovery of enterocyte damage and its clinical consequences. Serum intestinal fatty acid binding protein (I‐FABP) is a sensitive marker to study enterocyte damage. Aims To evaluate the severity of enterocyte damage in adult‐onset CD and its course upon a gluten‐free diet (GFD). Furthermore, the correlation among enterocyte damage, CD autoantibodies and histological abnormalities during the course of disease is studied. Methods Serum I‐FABP levels were determined in 96 biopsy‐proven adult CD patients and in 69 patients repeatedly upon a GFD. A total of 141 individuals with normal antitissue transglutaminase antibody (IgA‐tTG) levels served as controls. I‐FABP levels were related to the degree of villous atrophy (Marsh grade) and IgA‐tTG. Results I‐FABP levels were elevated in untreated CD (median 691 pg/mL) compared with controls (median 178 pg/mL, P < 0.001) and correlated with Marsh grade (r = 0.265, P < 0.05) and IgA‐tTG (r = 0.403, P < 0.01). Upon a GFD serum levels decreased significantly, however, not within the range observed in controls, despite the common observed normalisation of IgA‐tTG levels and Marsh grade. CD patients with elevated I‐FABP levels nonresponding to GFD showed persistent histological abnormalities. Conclusions Enterocyte damage assessed by serum I‐FABP correlates with the severity of villous atrophy in coeliac disease at the time of diagnosis. Although enterocyte damage improves upon treatment, substantial enterocyte damage persists despite absence of villous atrophy and low IgA‐tTG levels in the majority of cases. Elevated I‐FABP levels nonresponding to gluten‐free diet are indicative of histological abnormalities and warrant further evaluation.